2019
DOI: 10.1016/j.jtho.2018.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and Outcome of Elderly Patients Treated in the Concurrent Once-Daily Versus Twice-Daily Radiotherapy (CONVERT) Trial

Abstract: IntroductionThere is a lack of data on the efficacy and safety of concurrent chemoradiotherapy in elderly, limited-stage, patients with SCLC.MethodsWe compared outcomes of patients 70 years of age or older versus younger patients within the Concurrent Once-daily Versus twice-daily RadioTherapy (CONVERT) trial. Patients were randomized to receive 45 Gy/30 twice-daily fractions/19 days or 66 Gy/33 once-daily fractions/45 days concurrently with platinum-based chemotherapy. Overall survival and progression-free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 37 publications
1
32
1
Order By: Relevance
“…In our series, age was associated with an adverse outcome using 65 years as cut off. This is in contrast to a second analysis of CONVERT study which showed no impact of age using cut of 70 years [20].…”
Section: Discussioncontrasting
confidence: 99%
“…In our series, age was associated with an adverse outcome using 65 years as cut off. This is in contrast to a second analysis of CONVERT study which showed no impact of age using cut of 70 years [20].…”
Section: Discussioncontrasting
confidence: 99%
“…In LS-SCLC, the concurrent CTRT with modern radiotherapy techniques could be a treatment option for fit, older patients. This approach yields equivalent mOS in older vs younger patients (29 vs 30 months; p = 0.38) [37].…”
Section: Treatment Of Fragile and Elderly Patientsmentioning
confidence: 94%
“…4 Dr. Arjyal urges caution in the use of full-dose chemotherapy in elderly patients because of concerns about the higher risk of chemotherapy-related toxicity. 1 We fully agree with this view and would like to highlight that the suitability of elderly patients with limited-stage (LS) SCLC for chemoradiotherapy should be carefully assessed before treatment by a multidisciplinary team. However, patients should not be denied treatment purely on the basis of their physiological age but offered the treatment best suited to their biological and functional status.…”
Section: Chemoradiation In Elderly Patients With Limited-stage Small mentioning
confidence: 64%
“…To the Editor: Christodoulou et al compared outcomes of elderly (70 years of age) and younger patients (<70 years) with once-daily versus twice-daily radiation and concurrent chemotherapy in limited-stage SCLC. 1 The results were encouraging and supported chemoradiotherapy for fit, older patients. The study showed that fewer older patients received the optimal radiation treatments and had a higher rate of grade 3 or 4 neutropenia but the rates of chemotherapy compliance, neutropenic sepsis, and death were similar in both groups.…”
Section: Chemoradiation In Elderly Patients With Limited-stage Small mentioning
confidence: 79%
See 1 more Smart Citation